2019
DOI: 10.3390/foods8070246
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Compounds and Biological Functions of Garlic (Allium sativum L.)

Abstract: Garlic (Allium sativum L.) is a widely consumed spice in the world. Garlic contains diverse bioactive compounds, such as allicin, alliin, diallyl sulfide, diallyl disulfide, diallyl trisulfide, ajoene, and S-allyl-cysteine. Substantial studies have shown that garlic and its bioactive constituents exhibit antioxidant, anti-inflammatory, antibacterial, antifungal, immunomodulatory, cardiovascular protective, anticancer, hepatoprotective, digestive system protective, anti-diabetic, anti-obesity, neuroprotective, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
360
0
14

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 540 publications
(436 citation statements)
references
References 159 publications
5
360
0
14
Order By: Relevance
“…Alliinase causes the breakdown of alliin to form various volatile sulfur compounds like diallyl sulfide and diallyl disulfide [18,19]. Other reported compounds in the alliums are saponins and polyphenols, which contribute to the bioactivity of allium plant extracts [18][19][20]. In addition, previous phytochemical studies of garlic revealed the presence of eugenol diglycosides and β-carboline alkaloids with biological activities [20,21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alliinase causes the breakdown of alliin to form various volatile sulfur compounds like diallyl sulfide and diallyl disulfide [18,19]. Other reported compounds in the alliums are saponins and polyphenols, which contribute to the bioactivity of allium plant extracts [18][19][20]. In addition, previous phytochemical studies of garlic revealed the presence of eugenol diglycosides and β-carboline alkaloids with biological activities [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…A major sulfur-containing compound in garlic is S-allyl-L-cysteine sulfoxide (alliin) [17], which forms complexes with the enzyme alliinase, following crushing, cutting, or grinding of garlic bulbs [3]. Alliinase causes the breakdown of alliin to form various volatile sulfur compounds like diallyl sulfide and diallyl disulfide [18,19]. Other reported compounds in the alliums are saponins and polyphenols, which contribute to the bioactivity of allium plant extracts [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, garlic has antioxidant effects, mainly because of its diverse bioactive compounds, including allicin, diallyl sulphide (DAS), diallyl disulphide (DADS), S‐allylcysteine (SAC), saponins, micronutrients, and more than 20 phenolic compounds 14 . Scientific studies have demonstrated that the mechanism of antioxidative action of garlic might result from an enhancement of antioxidant enzyme activities and the regulation of the Nrf2‐ARE (nuclear factor erythrobia‐2 related factor 2‐ antioxidant response element) pathway 15 . Given the antioxidant effects of garlic, this plant can be considered as an appropriate alternative anti‐arthritis agent.…”
Section: Introductionmentioning
confidence: 99%
“…Bioactive compounds in food have attracted much attention as a safe and effective molecular library. It has reported that garlic is an excellent natural source of bioactive compounds( 28 ). In this study, we revealed that the beneficial effects of Allicin on energy homeostasis in obese mice.…”
Section: Discussionmentioning
confidence: 99%